The Effect of the Platelet Administration for the Patients with Liver Dysfunction after Liver Resection: Preliminary Clinical Trial - Hui Xu; Yu-Mei Li; Yongxiang Yi; Yun-Wen Zheng; Nobuhiro Ohkohchi (Case Reports in Gastrointestinal Medicine)
The aim of this study is to investigate the effect of platelet on the improvement of deteriorated liver function after liver resection. Six patients with hepatocellular carcinoma and liver cirrhosis have received the partial hepatectomy in the institution. Their Child–Pugh grade was B, and platelet count was below 7,000/µl. After hepatectomy, 20 units of platelet transfusion were carried out, liver function and side effects were investigated after 4 weeks, and the number of platelets increased to approximately 15,000/µl. Liver functions, such as aspartate transaminase (AST), alanine aminotransferase (ALT), cholinesterase (ChE), and prothrombin time, as well as albumin, recover to the same level as those before operation and 4 weeks after the operation. Any side effects were not recognized in all patients. Administration of platelets for cirrhotic patient with hepatectomy was carried with safety. But remarkable effect on the improvement of liver function was not recognized.